2017
DOI: 10.1007/s00059-017-4563-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of tolvaptan vs. furosemide in older patients with heart failure

Abstract: In older patients, tolvaptan relieves WRF, reduces the hospitalization period, and increases urine volume without significant effects on blood pressure. However, surprisingly, the use of tolvaptan did not influence 6‑month all-cause mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Xiong, et al 10) observed improvements in body weight and urine volume after tolvaptan therapy; however, serum creatinine levels significantly increased. On the contrary, Huang, et al 14) studied patients aged !65 years with acute heart failure and reported that tolvaptan significantly increased urine volume within 3 days of therapy and significantly decreased the rate of worsening of renal function. This discrepancy may be due to the difference in the dose of tolvaptan; four of the five studies included in the analysis of serum creatinine level by Xiong, et al 10) used a tolvaptan dose of at least 30 mg/day, whereas all six studies included in the analysis by Huang, et al 14) used a dose of 7.5-15 mg/day.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Xiong, et al 10) observed improvements in body weight and urine volume after tolvaptan therapy; however, serum creatinine levels significantly increased. On the contrary, Huang, et al 14) studied patients aged !65 years with acute heart failure and reported that tolvaptan significantly increased urine volume within 3 days of therapy and significantly decreased the rate of worsening of renal function. This discrepancy may be due to the difference in the dose of tolvaptan; four of the five studies included in the analysis of serum creatinine level by Xiong, et al 10) used a tolvaptan dose of at least 30 mg/day, whereas all six studies included in the analysis by Huang, et al 14) used a dose of 7.5-15 mg/day.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Huang, et al 14) studied patients aged !65 years with acute heart failure and reported that tolvaptan significantly increased urine volume within 3 days of therapy and significantly decreased the rate of worsening of renal function. This discrepancy may be due to the difference in the dose of tolvaptan; four of the five studies included in the analysis of serum creatinine level by Xiong, et al 10) used a tolvaptan dose of at least 30 mg/day, whereas all six studies included in the analysis by Huang, et al 14) used a dose of 7.5-15 mg/day. Under this dose, Huang, et al 14) concluded that tolvaptan reduced the worsening of renal function in older patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 It suppresses the synthesis and insertion of aquaporin-2 water channels into the luminal plasma membrane of collecting tubule principle cells, resulting in the restriction of water reabsorption in the hypertonic medulla without renal function deterioration. 1,4 Tolvaptan has a beneficial effect on patients in whom other diuretics, including loop diuretics, are ineffective; however, the US Food and Drug Administration (FDA) has issued a warning about the adverse effects of severe hypernatraemia and potentially fatal liver injury. 5…”
Section: Introductionmentioning
confidence: 99%